1966
DOI: 10.1002/cne.901280304
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal components of the optic nerve of the crayfish as studied by single unit analysis

Abstract: Unit responses were obtained from the optic nerve of the crayfish, Procambarus clarki (Girard) with steel needles. Eighty-three repeatedly recognized elements are described. They range from bundles of primary sensory fibers to complexly reacting multimodal interneurons. Visually reacting fibers fall into two main classes, one class reacts tonically to overall illumination, the other responds to moving objects. Sustaining fibers react to increased light with increased output, dimming fibers are active in the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…P. clarkii are sensitive to moving visual stimuli over a velocity range of at least four orders of magnitude (Glantz, 2001), indicating that motion detection is a critical component of the crayfish visual system. A significant portion of the primary visual synapse (Glantz and Bartels, 1994) and the ascending optic tract (Wiersma and Yamaguchi, 1966) are devoted to motion sensitivity. Glantz (Glantz, 2001) proposed that the polarization sensitive-neurons might also contribute to this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…P. clarkii are sensitive to moving visual stimuli over a velocity range of at least four orders of magnitude (Glantz, 2001), indicating that motion detection is a critical component of the crayfish visual system. A significant portion of the primary visual synapse (Glantz and Bartels, 1994) and the ascending optic tract (Wiersma and Yamaguchi, 1966) are devoted to motion sensitivity. Glantz (Glantz, 2001) proposed that the polarization sensitive-neurons might also contribute to this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…First, evidence reported by Wiersma (1970aj suggests that the defense reflex receives substantial input from the previously documented (Wiersma and Yamaguchi, 1967a) space constant motion detectors. Secondly, preliminary studies in this laboratory have consistently indicated that the stimulus conditions (e.g., discontinuous motion of dark objects) necessary to elicit the defense reflex are very similar t o the optimal conditions for eliciting activity in the jittery motion detectors (Wiersma and Yamaguchi, 1966). Furthermore, the motion detectors of the crayfish are known to undergo pronounced habituation with repeated stimulation to the same retinal area Yamaguchi, 1966,1967aj.…”
Section: Glantzmentioning
confidence: 98%
“…In crayfish, a class of visual interneurones known as sustaining fibres, initially called tonic 'on' neurones by Wiersma and Yamaguchi (Wiersma and Yamaguchi, 1966;Wiersma and Yamaguchi, 1967), have their main dendritic tree in the medulla (Kirk et al, 1982) and respond to a light pulse with a phasotonic discharge that persists for the duration of the stimulus and is followed by an inhibitory 'off' response (Kirk et al, 1983;Pfeiffer and Glantz, 1989). They are additionally directionally selective to movement (Glantz et al, 1995) (Fig.7A) and the response to light pulses (Fig.9A) are identical to those described above for such fibres.…”
Section: Identity Of the Populations Of Medulla And Lobula Neurones Wmentioning
confidence: 99%
“…Early work identified response properties of interneurones of the optic nerve to simple stimuli. These included sustaining fibres, dimming fibres and several classes of motion detectors (Waterman et al, 1964;Wiersma, 1966;Wiersma and Yamaguchi, 1966;Wiersma and Yamaguchi, 1967;York and Wiersma, 1975) (reviewed in Wiersma et al, 1982). Subsequent studies based on intracellular recording and Lucifer Yellow injections confirmed the identity of many of the sustaining fibres (Kirk et al, 1982;Kirk et al, 1983).…”
Section: Introductionmentioning
confidence: 99%